The essential role of thoracic duct embolization in management of traumatic iatrogenic chylothorax - Bruno Pagnin Schmid; Guilherme Moratti Gilberto; Marcela Juliano Silva Cunha; Leonardo Guedes Moreira Valle; Gustavo Foronda; Santiago Raul Arrieta; Felipe Nasser; Rodrigo Gobbo Garcia (Jornal Vascular Brasileiro, 2023)
Abstract This study aims to describe a case series of patients who underwent thoracic duct embolization (TDE) to treat traumatic iatrogenic chylothorax (TIC). Three patients were included: Case #1, a 49-year-old woman with follicular lymphoma developed a TIC following video-assisted thoracoscopic surgery to resect a solid right paravertebral mass and was treated with TDE using microcoils and N-butyl cyanoacrylate (NBCA) glue. Case #2, a 68-year-old man with cardiac amyloidosis developed a TIC following heart transplantation and was treated with TDE using microcoils and ethylene vinyl alcohol copolymer. Case#3: A 6-year-old patient with congenital heart disease developed a TIC following a Fontan procedure and was treated with TDE using NBCA glue. All lesions were identified during lymphangiography and TDE was successfully performed in all cases. TDE is a safe and valuable technique that provides minimally invasive treatment for TCI.